Convenient synthesis of the pentasaccharide repeating unit corresponding to the cell wall O-antigen of Escherichia albertii O4 - Manna, Tapasi; Gucchait, Arin; Misra, Anup Kumar (Beilstein Journal of Organic Chemistry, 2020)
A straightforward sequential synthetic strategy has been developed for the synthesis of a pentasaccharide repeating unit corresponding to the cell wall O-antigen of the Escherichia albertii O4 strain in very good yield with the desired configuration at the glycosidic linkages using thioglycosides and trichloroacetimidate derivatives as glycosyl donors and perchloric acid supported over silica (HClO4/SiO2) as a solid supported protic acid glycosyl activator. The expected configuration at the glycosidic linkages was achieved using a reasonable selection of protecting groups in the manosaccharide intermediates.
Keywords: Escherichia albertii O4; glycosylation; HClO4/SiO2; O-antigen; pentasaccharide

(untitled) - Mokomane, M.; Kasvosve, I.; de Melo, E.; Pernica, J. M.; Goldfarb, D. M. (Ther. Adv. Infect. Dis., 2018)

(untitled) - Heredia, N.; García, S. (Anim. Nutr., 2018)

(untitled) - Baker, S.; The, H. C. (Curr. Opin. Infect. Dis., 2018)

(untitled) - Kariuki, S.; Revathi, G.; Kariuki, N.; Kiiru, J.; Mwituria, J.; Hart, C. A. (BMC Microbiol., 2006)

(untitled) - Nataro, J. P.; Kaper, J. B. (Clin. Microbiol. Rev., 1998)

(untitled) - Nimri, L. F. (Diagn. Microbiol. Infect. Dis., 2013)

(untitled) - Huys, G.; Cnockaert, M.; Janda, J. M.; Swings, J. (Int. J. Syst. Evol. Microbiol., 2003)

(untitled) - Sharma, M.; Kniel, K. E.; Derevianko, A.; Ling, J.; Bhagwat, A. A. (Appl. Environ. Microbiol., 2007)

(untitled) - Yamamoto, D.; Hernandes, R. T.; Liberatore, A. M. A.; Abe, C. M.; de Souza, R. B.; Romão, F. T.; Sperandio, V.; Koh, I. H.; Gomes, T. A. T. (PLoS One, 2017)

(untitled) - Silhavy, T. J.; Kahne, D.; Walker, S. (Cold Spring Harbor Perspect. Biol., 2010)

(untitled) - Naumenko, O. I.; Zheng, H.; Senchenkova, S. N.; Wang, H.; Li, Q.; Shashkov, A. S.; Wang, J.; Knirel, Y. A.; Xiong, Y. (Carbohydr. Res., 2017)

(untitled) - Zarei, A. E.; Almehdar, H. A.; Redwan, E. M. (J. Immunol. Res., 2016)

(untitled) - Verez-Bencomo, V.; Fernández-Santana, V.; Hardy, E.; Toledo, M. E.; Rodríguez, M. C.; Heynngnezz, L.; Rodriguez, A.; Baly, A.; Herrera, L.; Izquierdo, M.; Villar, A.; Valdés, Y.; et al. (Science, 2004)

(untitled) - McCarthy, P. C.; Sharyan, A.; Moghaddam, L. S. (Vaccine, 2018)

(untitled) - Reglinski, M.; Ercoli, G.; Plumptre, C.; Kay, E.; Petersen, F. C.; Paton, J. C.; Wren, B. W.; Brown, J. S. (npj Vaccines, 2018)

(untitled) - Kaplonek, P.; Khan, N.; Reppe, K.; Schumann, B.; Emmadi, M.; Lisboa, M. P.; Xu, F.-F.; Calow, A. D. J.; Parameswarappa, S. G.; Witzenrath, M.; Pereira, C. L.; Seeberger, P. H. (Proc. Natl. Acad. Sci. U. S. A., 2018)

(untitled) - Kay, E.; Cuccui, J.; Wren, B. W. (npj Vaccines, 2019)

(untitled) - Berti, F.; Adamo, R. (Chem. Soc. Rev., 2018)

(untitled) - Bhatia, S.; Dimde, M.; Haag, R. (Med. Chem. Commun., 2014)

(untitled) - Shit, P.; Gucchait, A.; Misra, A. K. (Tetrahedron, 2019)

(untitled) - Chernyak, A.; Oscarson, S.; Turek, D. (Carbohydr. Res., 2000)

(untitled) - Sun, J.; Han, X.; Yu, B. (Synlett, 2005)

(untitled) - Zhang, J.; Mao, J.; Chen, H.; Cai, M. (Tetrahedron: Asymmetry, 1994)

(untitled) - Hendel, J. L.; Wang, J.-W.; Jackson, T. A.; Hardmeier, K.; De Los Santos, R.; Auzanneau, F.-I. (J. Org. Chem., 2009)

(untitled) - Kihlberg, J. O.; Leigh, D. A.; Bundle, D. R. (J. Org. Chem., 1990)

(untitled) - Mukhopadhyay, B.; Collet, B.; Field, R. A. (Tetrahedron Lett., 2005)

(untitled) - Mukherjee, C.; Misra, A. K. (Synthesis, 2007)

(untitled) - Chakraborti, A. K.; Gulhane, R. (Chem. Commun., 2003)

Indian Pat. Appl. - Chakraborti, A. K.; Gulhane, R. (A Process for the Acylation of Various Substrates using a Solid Support Catalyst, 2003)

(untitled) - Zemplén, G. (Ber. Dtsch. Chem. Ges. B, 1926)

(untitled) - Mukhopadhyay, B.; Maurer, S. V.; Rudolph, N.; van Well, R. M.; Russell, D. A.; Field, R. A. (J. Org. Chem., 2005)

(untitled) - Madhusudan, S. K.; Agnihotri, G.; Negi, D. S.; Misra, A. K. (Carbohydr. Res., 2005)

(untitled) - Oikawa, Y.; Yoshioka, T.; Yonemitsu, O. (Tetrahedron Lett., 1982)

(untitled) - Shangguan, N.; Katukojvala, S.; Greenberg, R.; Williams, L. J. (J. Am. Chem. Soc., 2003)

(untitled) - Lee, H.-H.; Schwartz, D. A.; Harris, J. F.; Carver, J. P.; Krepinsky, J. J. (Can. J. Chem., 1986)

(untitled) - Pearlman, W. M. (Tetrahedron Lett., 1967)